2017
DOI: 10.1007/s13205-016-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

RAPD assisted selection of black gram (Vigna mungo L. Hepper) towards the development of multiple disease resistant germplasm

Abstract: Black gram (Vigna mungo L. Hepper), is an extensively studied food crop which is affected by many abiotic and biotic factors, especially diseases. The yield potential of Black gram is shallow due to lack of genetic variability and biotic stress susceptibility. Core biotic stress factors include mung bean yellow mosaic virus (MYMV), urdbean leaf crinkle virus (UCLV), wilt (Fusarium oxysporum) and powdery mildew (Erysiphe polygoni DC). Although many studies determine resistant varieties to a particular disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Ali et al [15] reported RAPD markers for characterization of rust resistance in sugarcane. Vishalakshi et al [16] showed RAPD assisted Black gram germplasm selection for multiple disease resistance. Nair et al [10,17] and Ardiel et al [17] have shown the utility of RAPD analysis in identifying DNA sequence variations with resistance and susceptibility by converting them into SCAR markers.…”
Section: Primer Selectionmentioning
confidence: 99%
“…Ali et al [15] reported RAPD markers for characterization of rust resistance in sugarcane. Vishalakshi et al [16] showed RAPD assisted Black gram germplasm selection for multiple disease resistance. Nair et al [10,17] and Ardiel et al [17] have shown the utility of RAPD analysis in identifying DNA sequence variations with resistance and susceptibility by converting them into SCAR markers.…”
Section: Primer Selectionmentioning
confidence: 99%
“…Such comparative studies in legumes involving RAPD and ISSR markers have been successfully carried out previously in crops like Black gram (Souframanien and Gopalakrishna 2004), Vigna species (Dikshit et al 2007) and Rice (Ravi et al 2003). Also, RAPD markers has been used to study the genetic interraltionships among blackgram genotypes to develop multidisease resistance germplasm (Vishalakshi et al 2017).…”
Section: Diseases Reaction Of Genotypesmentioning
confidence: 99%
“…The thermotolerant yeast Kluyveromyces marxianus is a promising candidate for fuel ethanol production as it possesses several advantageous characteristics for biotechnological applications such as the faster growth rate relative to Kluyveromyces lactis [ 1 ] or Saccharomyces cerevisiae [ 2 ], the ability to assimilate a wide range of sugars [ 3 ], thermotolerance [ 4 6 ], secretion of lytic enzymes and the ability to produce ethanol at elevated temperatures [ 7 ]. Specifically, K .…”
Section: Introductionmentioning
confidence: 99%